Gone With the Modern Wind? The National Identity, Democracy, and the University in the Global Age - Kwiek, Marek (My University, 2000)
Widely conceived processes of globalization bring about transformations of an unprecedented nature and scale. I hr world we have been thinking about in philosophy, sociology, political sciences, political economy - that is to say, depending on the discipline: the modern world founded on reason and rationality, social communication and dreams of the social order, the world separated into national entities and closed in the formula ol tin "nation-state", the world of a social contract in which there is a strict conned ion between welfare state, capitalism, and democracy, finally, the world in which thru is a clear priority of politics to economy - is disintegrating right before our eyes together with the gradual passage to the global age. Therefore today, the questions about democracy may require a deliberation in a different vocabulary: the vocabulary that would be able to break away from the less and less socially appealing myth that was at the foundations of modern social sciiences, according to which we keep analyzing the world in which the primary point of reference is the territorially-bound nation-state.
Keywords: modern university; modernity; globalization; public sector; nation-state; democracy